PCR-screening of clinical blood samples the presence of BLV-, BIV-, BFV-infected animals in the farms of the eastern region of Ukraine - Lymanska, O.; Kulyk, I.; Zlenko, O.; Rudova, N.; Horbatenko, S.; Gerilovych, A. (Agricultural Science and Practice, 2017)
Retrovirus infections of cattle, including leukemia, are widespread in the whole world. In Ukraine, leukemia has been investigated for over 40 years, whereas minor retroviruses of cattle have not been studied yet. Aim. PCR-screening of samples of bovine peripheral blood, subject to diagnostic studies of leukemia, from the farms in the Eastern Ukraine (Kharkiv and Sumy regions). Methods. The genetic material of agents of retroviral infections in clinical samples was detected via conventional PCR and real-time PCR. Results of Investiga- tions. The presence of BLV-, BIV-, BFV-infected animals among livestock was established. The number of animals, infected with leukemia, was 57–100 % from the total number of examined livestock on average. The presence of genetic material of BIV virus was either not detected at all, or detected in the amount of 62 % from the number of tested animals. At the same time, the presence of genetic material of BFV was in the range of 61.5–81 % from the total number of studied samples. A possible connection between the viruses of leukemia, immunodefi ciency and foamy virus of cattle, circulating among the livestock in the farms of the Eastern region of Ukraine, was also established. Conclusions. The presence of genetic material of immunodefi ciency virus in the leukemia-positive samples was insignifi cant – only 4 samples, whereas the presence of the foamy virus in the leukemia-positive samples was detected in 51 samples, which was 3 % and 42 % from the total number of investigated samples respectively. The absence of leukemia virus in the blood samples, containing the DNAs of two other minor retroviruses, was detected in one sample (0.8 %). The simultaneous presence of all three agents of retroviral infections was established in 36 samples (30 %).